2017
DOI: 10.5897/ijlp2016.0325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of equine strongyle infection and its associated risk factors in Jimma Town, Southwest Ethiopia

Abstract: This cross-sectional study was carried out from November, 2015 to May, 2016 to determine the prevalence of equine strongyles and associated risk factors in Jimma town. Fresh faecal samples were obtained from 384 randomly selected horses (n= 287), donkeys (n= 67) and mules (n= 30). Coprological examination for the detection of strongyle eggs was performed using floatation technique. The overall prevalence of strongyle infection in all species of animals was found to be 26.56% (102/384). The infection rate was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Concerning cestodes, Getachew (2006) also showed that there is no association between age and tapeworm infection prevalence in horses. Sori et al (2017) indicated that sex was not associated with the prevalence of equine strongylosis, possibly because the management is the same regardless of the sex class (Tone et al, 2016). The insignificant difference in nematode egg counts between male and female donkeys could be due to the fact that they were reared and grazed on the same pasture (Tone et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning cestodes, Getachew (2006) also showed that there is no association between age and tapeworm infection prevalence in horses. Sori et al (2017) indicated that sex was not associated with the prevalence of equine strongylosis, possibly because the management is the same regardless of the sex class (Tone et al, 2016). The insignificant difference in nematode egg counts between male and female donkeys could be due to the fact that they were reared and grazed on the same pasture (Tone et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the possible explanation for nonsignificant differences in terms of GIP infection prevalence and intensity between male and female donkeys could be attributed to the mutual grooming behavior of donkeys that could play a role in transmitting the infection between members of a herd. On the other hand, there are reported cases of the high prevalence of strongylosis in males compared to females despite the fact that the differences were not significant (Sori et al, 2017). The possible reason might be due to the workload done by males than females, which causes stress and consequent immune-suppression which results in parasitic burden (Regassa and Yimer, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the infection is associated with loss of digestive function, decreased fertility and poor body condition of animals (Brady and Nichols 2009). Among different groups of the helminths, large strongyles are the most pathogenic gastrointestinal parasites of equines (Sori et al 2017). A number of studies conducted to detect an association between poverty and animal diseases have identified gastrointestinal parasitism as one of the most important problems for equids in developing countries (Mezgebu et al 2013).…”
Section: Introductionmentioning
confidence: 99%